PENGEMBANGAN E-BOOK INTERAKTIF BERBASIS MIND MAPPING MATA PELAJARAN LAYANAN LEMBAGA KEUANGAN SYARIAH KELAS XII SMK - Rahmah, Cheyzara; Hakim, Luqman (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to develop an e-book product for learning Islamic financial institution service courses. This development is a Research and Development research. This development uses Thiagarajan, Semmel and Semmel's 4D models including define, design, develop, and disseminate steps. This study resulted in a feasibility test of material, language, graphic experts and student responses to the use of e-books. From these results, it is known that mind mapping-based interactive e-books based on Android devices using a scientific approach are very suitable for use in learning activities. The times have reduced the boundaries between the digital world and the physical world in many areas of human life, including the world of education. The 2013 revised edition of the curriculum, which is the latest change in the education curriculum in Indonesia, must always be balanced with the development of learning tools, including teaching materials. This research & development research has the aim of developing teaching materials in the form of interactive e-books based on Android devices for LLKS subjects with a scientific approach.